SENTENCE STRUCTURE AND SYNTAX IN OLD ENGLISH - Ergashev Farruxbek Ortiqboy o'g'li (TADQIQOTLAR, 2025)
Abstract: This paper examines the sentence structure and syntactic organization of Old English as used between the 5th and 11th centuries. Using a descriptive- historical linguistic approach, the study investigates how casebased morphology, flexible word order, and the absence of rigid syntactic rules shaped clause formation in Old English prose and poetry. Analysis of religious, legal, and poetic texts shows that the inflectional system allowed variation such as OV and VO patterns, while subordinating conjunctions and relative markers signaled clause relationships without depending strictly on word position. The results indicate that syntactic flexibility in Old English was structurally sustained by rich inflection rather than word order constraints. Furthermore, the coexistence of Germanic syntactic inheritance and emerging Latin-influenced constructions reflects a transitional phase that paved the way for Middle English syntactic stabilization. The findings suggest that Old English syntax represents a key stage in the diachronic development of English sentence structure, linking morphologically governed and positiongoverned grammatical systems.